Distribution System Optimization Starts with Data. Issue 6 (1st June 2013) - Martin, Barb; Ries, Tom
Abstract : Although producing safe drinking water at treatment plants is highly regulated, only a limited but increasing number of regulations directly apply to distribution systems. The regulations exist to ensure delivery of safe water to consumers, providing an additional layer of public health protection after water leaves the water treatment plant.